Key technology upgrade and application development of Guizhou red sour soup industry - QIN Weijun, BAO Aiming, CHEN Xingxing, QIN Likang, LIU Na, HU Yue (Zhongguo niangzao, 2024)
Guizhou red sour soup is a traditional food of ethnic minorities in Guizhou with a history of thousands of years for eating, which was a unique sour condiment. The development status of the sour soup industry, key technology of modern fermentation, the integration technology upgrade of standardization, mechanization, digital intelligence, and application development of sour soup were analyzed. The raw materials pretreatment, microbial community structure, enhanced fermentation technology, digital intelligence technology, sterilization technology, and so on were emphatically elaborated. It was pointed out that the industrial application development of red sour soup should be promoted from the aspects of expanding application scenarios and brand construction. The upgrade and application development status of key technologies in sour soup industry were reviewed, in order to provide reference ideas for the development of sour soup industry.